History of Industrial Gases - Almqvist, Ebbe. author. aut Link
XVIII, 472 p.
Keywords: Starting at the dawn of science, History of Industrial Gases traces the development of gas theory from its Aristotelian roots to its modern achievements as a global industry. Dr. Almqvist explores how environmental protection, geographical areas, and the drive for higher purity and efficiency affected development in the nineteenth and twentieth centuries, and how they will influence the future of this rapidly expanding industry. The roles of major contributing companies are also discussed to provide an informative and thought-provoking treatise valuable to anyone who studies or works in this fascinating field.